Dietary restraint and impulsivity modulate neural responses to food in adolescents with obesity and healthy adolescents. (18th September 2015) - Hofmann, Johannes; Ardelt‐Gattinger, Elisabeth; Paulmichl, Katharina; Weghuber, Daniel; Blechert, Jens
Abstract : Objective: Despite alarming prevalence rates, surprisingly little is known about neural mechanisms underlying eating behavior in juveniles with obesity. To simulate reactivity to modern food environments, event‐related potentials (ERP) to appetizing food images (relative to control images) were recorded in adolescents with obesity and healthy adolescents. Methods: Thirty‐four adolescents with obesity (patients) and 24 matched healthy control adolescents watched and rated standardized food and object images during ERP recording. Personality (impulsivity) and eating styles (trait craving and dietary restraint) were assessed as potential moderators. Results: Food relative to object images triggered larger early (P100) and late (P300) ERPs. More impulsive individuals had considerably larger food‐specific P100 amplitudes in both groups. Controls with higher restraint scores showed reduced food‐specific P300 amplitudes and subjective palatability ratings whereas patients with higher restraint scores showed increased P300 and palatability ratings. Conclusions: This first ERP study in adolescents with obesity and controls revealed impulsivity as a general risk factor in the current obesogenic environment by increasing food‐cue salience. Dietary restraint showed paradoxical effects in patients, making them more vulnerable to visual food‐cues. Salutogenic therapeutic approaches that deemphasize strict dietary restraint and foster healthy food choice might reduce such paradoxical effects.